Platformisation of Science: Conceptual Foundations and Critical Perspectives for the Science System - Fecher, Benedikt; Kunz, Raffaela; Sokolovska, Nataliia; Wrzesinski, Marcel (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2024)
The digital platforms we are dealing with in this article are auxiliary tools that do not produce anything themselves but provide an infrastructure for service providers and users to meet. They have potentially unlimited scaling potential and have become the central places of exchange. In academia we can also observe that research and its communication becomes more digital  and that digital services are aiming to become platforms. In this article we explore the concept of digital platforms and their potential impact on academic research, firstly addressing the question: To what extent can digital platforms be understood as a specific type of research infrastructure? We draw from recent literature on platforms and platformisation from different streams of scholarship and relate them to the science studies concept of research infrastructures, to eventually arrive at a framework for science platforms. Secondly, we aim to assess how science platforms may affect scholarly practice. To this end, we relate common platform practices to scientific practice. Thirdly, we aim to assess to what extent science is platformized and how this interferes with scientific understandings of quality and autonomy. In the end of this article, we argue that the potential benefits of platform infrastructure for academic pursuits cannot be ignored, but the commercialization of the infrastructure for scholarly communication is a cause for concern. Ultimately, a nuanced and well-informed perspective on the impact of platformisation on academia is necessary to ensure that the academic community can maximize the benefits of digital infrastructures while mitigating negative consequences.